2021
DOI: 10.1108/ijpdlm-12-2020-0434
|View full text |Cite
|
Sign up to set email alerts
|

AI technologies and their impact on supply chain resilience during COVID-19

Abstract: PurposeCOVID-19 has pushed many supply chains to re-think and strengthen their resilience and how it can help organisations survive in difficult times. Considering the availability of data and the huge number of supply chains that had their weak links exposed during COVID-19, the objective of the study is to employ artificial intelligence to develop supply chain resilience to withstand extreme disruptions such as COVID-19.Design/methodology/approachWe adopted a qualitative approach for interviewing respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 47 publications
0
83
0
1
Order By: Relevance
“…IPT advocates that organizations have two strategies, reducing information processing needs and improving information processing capacity, which can be used to support decision making in times of uncertainty (Galbraith, 1973 ). IPT has been widely used in operations and supply chain management studies (Qrunfleh & Tarafdar, 2014 ; Fan et al, 2017 ), it and has the potential to explain the effect of supply chain disruption on the development of firm resilience during COVID-19 because the uncertainty of interference boosts the demand for information processing (Modgil et al, 2021 ; Dubey et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…IPT advocates that organizations have two strategies, reducing information processing needs and improving information processing capacity, which can be used to support decision making in times of uncertainty (Galbraith, 1973 ). IPT has been widely used in operations and supply chain management studies (Qrunfleh & Tarafdar, 2014 ; Fan et al, 2017 ), it and has the potential to explain the effect of supply chain disruption on the development of firm resilience during COVID-19 because the uncertainty of interference boosts the demand for information processing (Modgil et al, 2021 ; Dubey et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Dubey et al, 2021 ). Existing research on resilience based on IPT has indicated that identifying and integrating information needs and developing information processing capabilities play inestimable roles in embedding a high degree of resilience in firm operations (Modgil et al, 2021 ). In addition, customer integration, supplier integration and internal integration further reduce information processing requirements and enhance information processing capabilities through information management across functional departments and beyond organizational boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Azadegan and Dooley ( 2021 ) asserted that for supply network resilience, existing literature focused on private or micro-level collaborations. In addition, Modgil et al ( 2021 ) examined AI’s role in enhancing supply chain resilience through distribution capabilities, risk sourcing, and developing visibility. Thus, we propose the following propositions based on our findings and support literature.…”
Section: Implications and Framework Developmentmentioning
confidence: 99%
“…Supply chain resilience has been defined as "the adaptive capability of the supply chain to prepare for unexpected events, respond to disruptions and recover from them by maintaining continuity of operations at desired levels of connectedness and control over structure and function" (Ponomarov and Holcomb, 2009). This concept has received considerable scholarly attention in recent times (Modgil et al, 2022;G€ olgeci and Kuivalainen, 2020;Bag et al, 2019;Ali and G€ olgeci, 2019;Cheng and Lu, 2017). A group of scholars in this domain has identified several enablers/antecedents that can enhance firms' capabilities (Teece, 2018) in developing supply chain resilience such as visibility, collaboration (J€ uttner and Maklan, 2011), absorptive capacity (G€ olgeci and Kuivalainen, 2020) and supply chain reengineering (Gonz alez-Zapatero et al, 2021) to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain resilience has been defined as “ the adaptive capability of the supply chain to prepare for unexpected events, respond to disruptions and recover from them by maintaining continuity of operations at desired levels of connectedness and control over structure and function ” (Ponomarov and Holcomb, 2009) . This concept has received considerable scholarly attention in recent times (Modgil et al. , 2022; Gölgeci and Kuivalainen, 2020; Bag et al.…”
Section: Introductionmentioning
confidence: 99%